Use of formoterol in the treatment of stuttering. A pilot study - Pešák, Josef; Zapletalová, Jana; Grézl, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2009)
AIMS: Stuttering is a serious health and social problem that can distinctively affect not only the mental development of an individual but also his life possibilities, including social fulfilment and his general life prospects. The etiology of stuttering is however unknown and that is why it is not possible to treat it causally. This pilot study takes into account the hypothesis of bronchial constriction as a negative factor in stuttering and investigates the effect of the long-acting bronchodilator formoterol fumarate on stuttering in 42 patients. METHODS: Patients were divided in 2 groups - A (school children and juveniles) and B (adults 18-25 resistant to other treatment). The medicine was administered once a day in the morning in a dose of 12 microg for the total period of 6 months. The prime outcome parameter - severity of stuttering - was evaluated using the ordinary scale (McGill Pain Questionnaire). The evaluation was done by an examining physician during visits to the centres and by the patients themselves (in cases of the youngest with the assistance of a parent) in a daily diary. RESULTS: A non-parametric pair test (Wilcoxon signed rank test) was used to compare the average marks in the whole set of patients. During the six moth period of administration of Foradil the speech fluency improved. The average number of dysfluent words decreased from 10.5 +/- 1.3 to 6.6 +/-0.97. CONCLUSION: The average mark of speech fluency evaluated by the physicians between the period of non use of Foradil and the six month period after the use of Foradil improved from 2.95 +/- 0.76 to 1.95 +/- 0.56 (as proved by the chi-square test, p<0.0001). The evaluation of speech fluency of balbuties uses the logopedic practices. Other clinical evaluations of speech fluency are not known.
Keywords: rozvrh dávkování léků; financování organizované; dospělí; Female; dítě; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Pilot Projects; Bronchodilator Agents; Drug Administration Schedule; pilotní projekty; stupeň závažnosti nemoci; Financing, Organized; Male; ethanolaminy; Stuttering; Young Adult; Ethanolamines; Speech; Child; mužské pohlaví; koktavost; Severity of Illness Index; bronchodilatancia; mladiství; řeč; Humans